Ten practical guidelines for microclimate research in terrestrial ecosystems - Pieter De Frenne; Rémy Beugnon; David Klinges; Jonathan Lenoir; Pekka Niittynen; Sylvain Pincebourde; Rebecca A. Senior; Juha Aalto; Kryštof Chytrý; Phillipa K. Gillingham; Caroline Greiser; Eva Gril; et al. (Methods in Ecology and Evolution)
Abstract Most biodiversity dynamics and ecosystem processes on land take place in microclimates that are decoupled from the climate as measured by standardised weather stations in open, unshaded locations. As a result, microclimate monitoring is increasingly being integrated in many studies in ecology and evolution. Overviews of the protocols and measurement methods related to microclimate are needed, especially for those starting in the field and to achieve more generality and standardisation in microclimate studies. Here, we present 10 practical guidelines for ground‐based research of terrestrial microclimates, covering methods and best practices from initial conceptualisation of the study to data analyses. Our guidelines encompass the significance of microclimates; the specifics of what, where, when and how to measure them; the design of microclimate studies; and the optimal approaches for analysing and sharing data for future use and collaborations. The paper is structured as a chronological guide, leading the reader through each step necessary to conduct a comprehensive microclimate study. At the end, we also discuss further research avenues and development in this field. With these 10 guidelines for microclimate monitoring, we hope to stimulate and advance microclimate research in ecology and evolution, especially under the pressing need to account for buffering or amplifying abilities of contrasting microhabitats in the context of global climate change.